The Aglipayan Church sanctuary of the people in Buenavista, Guimaras during the Philippine revolution. - Palacios, Methoselah M.
This study aims to identify and describe the local conditions in Guimaras prior to the establishment of the first Aglipayan Church in the area ; to describe the problem within the hierarchy of the Aglipayan Church and to analyze the interaction between the first Aglipayan Missions and the locals that made it possible for the establishment of the Aglipayan Church in Buenavista